RELAY TESTER BERBASIS MIKROKONTROLER - Indah Rahmadini; Andrea Hera Andini; Surojo Surojo; Yudhi Yudhi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The component that is often used in practice is the relay. However, in practice, students often have problems when using relay components due to damaged relays. This happens because there is no tool to detect a damaged relay quickly. To overcome these problems, a microcontroller-based relay tester was made that can quickly check the feasibility of the relay. Which aims to detect a damaged relay quickly. Where the measurement process is by connecting the relay to the available socket, then the output on the relay will be processed by Arduino and the results will be displayed on the LCD and LED. The output on the relay is OK if it's still functioning and Error if it's damaged and the LED is for displaying the test light, if one of the lights goes out, it means the relay is an error, and if there's no damage, the lights will all turn on. From the results of testing more than 10 times testing the tool, it was found that the tool functions well and is accurate. Comparison data was also obtained when testing relays using a relay tester that was made, the time when checking only needed 01.18 seconds for every 1 relay. And for the 10x experiment of relay testing using a relay tester, alternating between 5-foot, 8-foot and 11-foot relays only takes 13.2 seconds.